IL-17A Can Promote Propionibacterium acnes-Induced Sarcoidosis-Like Granulomatosis in Mice - Song, Jiacui; Zhao, Mengmeng; Li, Qiuhong; Lu, Liqin; Zhou, Ying; Zhang, Yuan; Chen, Tao; Tang, Danli; Zhou, Nianyu; Yin, Chengsheng; Weng, Dong; Li, Huiping (Frontiers in Immunology, 2019)
The etiology of sarcoidosis is unknown. In this study, Propionibacterium acnes (PA) was used to induce sarcoidosis-like granulomatous inflammation in a mouse model. Wild-Type (WT) C57BL/6 mice were divided into three groups: (1) WT-PA group; (2) WT-PA+Incomplete Freund's Adjuvant (IFA) group; and (3) WT-PBS group. Loose granuloma formation was observed in the lungs on day 56 in the WT-PA and WT-PA +IFA groups. The proportions of peripheral Th17 cells in the WT-PA (p=0.0004) and WT-PA+IFA groups (p=0.0005) were significantly higher than that in the WT-PBS group. The proportions of peripheral Treg cells in the WT-PA (p<0.0001) and WT-PA+IFA groups (p<0.0001) were lower than that in the WT-PBS group. Then, to explore the mechanism of IL-17, Wild-Type (WT) C57BL/6 mice were divided into three groups: (1) WT-PBS group (2) WT-PA group; (3) WT-PA+mouse IL-17A neutralizing antibody (IL-17Ab) group. IL-17A gene knockout mice (KO) were divided into two groups: (1) KO -PA group; (2) KO-PBS group. The KO-PA and WT-PA + IL-17Ab groups showed reduced inflammation and no loose granuloma formation on day 56. As compared to the WT-PA group, the ratio of peripheral Th17 in the KO-PA (p<0.0001) and WT-PA + IL-17Ab groups (p<0.0001) decreased, while the ratio of peripheral Treg in the KO-PA (p<0.0001) and WT-PA+ IL-17Ab（p=0.0069）groups increased on day 56. Hence, PA can be used to establish a mouse model of sarcoidosis-like granuloma. IL-17A plays an important role in experimental sarcoidosis-like granuloma formation.